2019
DOI: 10.1111/ijmr.12206
|View full text |Cite
|
Sign up to set email alerts
|

Reinvigorating Research on Gender in the Workplace Using a Positive Work and Organizations Perspective*

Abstract: Gender inequality is a widespread organizational challenge, however, research on gender in the workplace suffers from stagnation in mainstream management research. A positive work and organizations perspective has the capacity to augment problem‐focused gender research with new approaches to boosting gender equity. Yet, contributions that utilize such a perspective are sparsely spread across nearly two decades’ time and dozens of journals with differing disciplinary foci. This paper aims to reinvigorate gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 117 publications
0
28
0
1
Order By: Relevance
“…PsyCap as a higher order construct has been shown to be an important predictor of employee workplace performance in modern organizations [ 10 , 11 , 15 ], while its individual components of hope, self-efficacy, resilience, and optimism have also been shown to be antecedents to a plethora of work outcomes, including high performance, work engagement, team cohesion, and return on investment [ 3 , 18 , 35 , 36 , 37 , 38 , 39 ]. One practical strength of this empirical evidence is that it clearly supports that PsyCap can be developed and can be used to design human resource development and positive organizational psychology interventions (POPIs) [ 10 , 11 , 15 ]).…”
Section: Discussionmentioning
confidence: 99%
“…PsyCap as a higher order construct has been shown to be an important predictor of employee workplace performance in modern organizations [ 10 , 11 , 15 ], while its individual components of hope, self-efficacy, resilience, and optimism have also been shown to be antecedents to a plethora of work outcomes, including high performance, work engagement, team cohesion, and return on investment [ 3 , 18 , 35 , 36 , 37 , 38 , 39 ]. One practical strength of this empirical evidence is that it clearly supports that PsyCap can be developed and can be used to design human resource development and positive organizational psychology interventions (POPIs) [ 10 , 11 , 15 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The direct result is a work climate in which women are discriminated against, as they are faced with the dilemma of having to choose between their professional careers and their work-life balance [18,69,78,79]. This is why, for a decade now, some authors have been arguing that organizations need to transform their cultural matrices: in other words, the set of norms that define commitment to one's job, success at work and proper behavior with regard to family commitments [3,[80][81][82]. Nevertheless, as pointed out by a significant part of the literature on the relationship between sustainability and organizational change [83,84], the emphasis placed by organizations in their search for a culture of sustainability focuses on issues associated with the environment, energy efficiency and their direct impact upon the surrounding community, all too often overlooking the importance of the work-life balance dimension.…”
Section: Wor-life Balance and Social Sustainabilitymentioning
confidence: 99%
“…Three of the SDGs directly target branches of science with ties to organizational studies (SDG 8: decent work and economic growth; SDG 9: industry, innovation and infrastructure; and SDG 12: responsible consumption and production). It is explicitly stated that these goals will come as an enormous challenge for organizations and will have a significant impact on them in terms of management [2][3][4]. Likewise, there are at least three other SDGs that prove relevant in this regard (SDG 5: gender equality; SDG 10: reduced inequalities; and SDG 11: sustainable cities and communities).…”
Section: Introductionmentioning
confidence: 99%
“…Warren et al (2017) suggested PWO uses concepts inspired by the positive psychology movement and within the three main strands of POS, POB, and POP (Seligman and Csikszentmihalyi 2000). Further, Warren et al (2019) proposed that the overall goal of PWO is to explicitly focus on psychological mechanisms that promote employee and organizational flourishing. While we acknowledge that other interventions have been developed to improve the workplace, the psychological mechanisms through which these interventions operate vary greatly.…”
Section: Need For Review Of Positive Psychology Interventions At Workmentioning
confidence: 99%